Influence of Tool Pin Profile on Mechanical Properties of Joint of Aluminium Alloys 2014 and 6082, Welded With Friction Stir Welding - Ashwani Kumar; Pardeep Kumar; Sidhu, Balwinder S. (Asian Review of Mechanical Engineering, 2013)
It is challenging to obtain defect free welded joints of Aluminum Alloys with the help of fusion welding processes. In fusion welding, oxide layer of aluminum alloys penetrate inside, which has the tendency to thicken at higher temperatures, which in turn results in the defects like porosity and cracks in the weld joint. In contrast, Friction Stir Welding (FSW) is proved to be a very good solid state welding technique, which has got a worldwide attraction, especially in aerospace industry. FSW doesn’t involve actual melting of the materials, rather the welding is done at visco-plastic state of the materials, which helps to reduce the heat affected zone in the weld joint and original characteristics of material are protected from getting changed, as far as possible. Combination of 2xxx series and 6xxx series of aluminum alloys are highly used in aerospace and automobile industry due to their good-strength to weight ratio, mechanical properties and anti-corrosion properties. The work has been done to improve the strength and quality of Friction Stir Welded joints by changing process parameters. Tool pin profile also has a great impact on the strength and quality of friction stir welded joints. The present paper investigates the influence of different pin profiles on the mechanical properties of dissimilar aluminum alloys, welded with FSW. Aluminum alloys 2014 and 6082 were successfully welded by using three (Square, Pentagon and Hexagon) different pin profiles. From the results, it was observed that that the joint fabricated by using pentagonal pin profiled tool given superior tensile and micro-hardness properties as compared to other joint.